Angle calibration and error analysis of wide-angle X-ray scattering (WAXS) with a one-dimensional linear detector. Issue 1 (31st December 2021) - Chen, Rongchao; Li, Zhihong; Shi, Ying; Liu, Li-Zhi; Wang, Yuexiang; Lv, Baoliang
Abstract: Wide-angle X-ray scattering (WAXS) is routinely used to characterize the ordered structure in materials. The measured angles are generally calibrated by using standard samples with several diffraction peaks. When a WAXS instrument uses a one-dimensional linear detector, which is tilted to the direct beam, the angle calibrations need three standard diffraction peaks. This contribution presents the corresponding analytical solution of the calibration equations and error estimation matrix and performs error simulation and experimental verification. The results show that the selected three standard diffraction peaks should uniformly span and widely cover the detector to reduce the error of angle calibration.